Case Report: Gastric-Type Endocervical Adenocarcinoma Mimicking Submucosal Myoma Under Hysteroscopy - Wang, Jiao; Yang, Qing; Wang, Dandan; Li, Mengyuan; Zhang, Ningning (Frontiers in Medicine, 2022)
Gastric-type endocervical adenocarcinoma (GAS) is considered a distinct and clinically important entity because it is unrelated to human papillomavirus infection and has aggressive behavior and worse clinical outcomes than the usual type of endocervical adenocarcinoma (ECA). The preoperative diagnosis of GAS is often difficult because of its nonspecific clinical manifestations and special lesion location. We report the case of a 50-year-old Chinese woman who presented with intermittent left lower abdominal pain for 1 year. Preoperative images showed left hydrosalpinx and a lesion that was mainly located in the lower part of the uterine cavity. We considered the lesion to be a polyp before surgery. During hysteroscopic surgery, we suspected that it may be a submucosal myoma. However, pathology revealed that it was a GAS. GAS may be located in the upper endocervix or even reach the uterine cavity. The appearance is occasionally similar to that of submucosal myoma, resulting in difficult preoperative diagnosis and even misdiagnosis.